2016
DOI: 10.2340/16501977-2124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acceleration and deceleration distance on the walking speed of people with chronic stroke

Abstract: Adoption of 1 m acceleration and deceleration distance is recommended when measuring the comfortable walking speed in the 5mWT in people with stroke. Neither acceleration nor deceleration distance is needed when measuring the maximum walking speed in the 5mWT, the comfortable walking speed or the maximum walking speed in the 10mWT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
7
1
1
Order By: Relevance
“…[41][42][43] The literature is scarce about the factors related to ability to increase walking speed. In our study the walking speed reserve was 20%, which is slightly lower than previous studies, 44,45 described between 25 to 50% in ambulatory after stroke with similar walking speed, and age (mean self-selected walking speed between 0.74m/ and 0.84m/s, and mean fast walking speed between 0.93m/s to 1.05m/s; mean age ranged 60 to 61 years). 44,45 One previous study found a significant association between balance (assessed by Berg Balance Scale) and walking speed reserve (r= 0.74) in individuals after stroke, demonstrating that besides muscle strength other variables may be related to ability to increase gait speed.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…[41][42][43] The literature is scarce about the factors related to ability to increase walking speed. In our study the walking speed reserve was 20%, which is slightly lower than previous studies, 44,45 described between 25 to 50% in ambulatory after stroke with similar walking speed, and age (mean self-selected walking speed between 0.74m/ and 0.84m/s, and mean fast walking speed between 0.93m/s to 1.05m/s; mean age ranged 60 to 61 years). 44,45 One previous study found a significant association between balance (assessed by Berg Balance Scale) and walking speed reserve (r= 0.74) in individuals after stroke, demonstrating that besides muscle strength other variables may be related to ability to increase gait speed.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies have investigated the individual role of muscles groups in predicting the walking speed. 4,44,[46][47][48] However, the relation between average strength of paretic side on walking speed and walking speed reserve was not well reported so far. Individuals after stroke show different strategies to activate the lower limb muscles to walk during self-selected, fast and, to increase walking speed.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the walking pattern alteration could be different during the aging process, and could also depend on testing conditions. The impact of the methods used to obtain walking/gait speed was also addressed by Ng et al 101 and Wang et al 102 To explain alterations of walking capacity and patterns, different hypotheses have been put forward. In the Baltimore Longitudinal Study of Aging, a significant correlation between walking speed and maximal voluntary contraction of knee extensor was shown.…”
Section: Physiological Changes In the Older Population: Sarcopenia Anmentioning
confidence: 99%
“…Selection of walk test protocols and reference values. Because walk test protocol features (e.g., distances [50,51]; walking aid used [52]; encouragement [53]) can influence performance, a single protocol for each walk test was developed to enable comparison across care settings. We used criteria (see Supplementary Material 1) to select and adapt protocols that would optimize measurement accuracy, applicability to people undergoing stroke rehabilitation, and implementation feasibility for hospital settings in terms of cost, space, and time.…”
Section: Use Of Theory To Design the Toolkit Implementation Strategy And Process Evaluationmentioning
confidence: 99%